Faculty of Operation and Economics of Transport and Communications - Tatiana Corejova (Communications - Scientific letters of the University of Zilina, 2003)
The Faculty of Operation and Economics of Transport and Communications provides university education and prepares specialists for solution of management, technology, economic problems and for business activities especially in sphere of transport, postal services, telecommunications as well as in sphere of business management and economics, banking industry and three-level education system of banking.